Multimodal Adaptation, Reconstruction, and Deviation of Immortal Ones - Xinzuo Li (Linguaculture)
Since time immemorial, immortal ones, or Shenxians in Chinese, have been an integral part of the Chinese civilization, reflecting the ancient and everlasting pursuit of immortality, both physically and spiritually. In particular, the epic novel Journey to the West offers a panoramic view of their hierarchy, personality, and ways of life. For this reason, the novel has been adapted into different multimedia versions. The animated comedy Monkey King (2023), produced by Netflix, is one of the recent but less satisfactory examples, in which the images of immortals are reconstructed in a multimodal manner suffering from adaptational deviation. Based on previous studies on translation, adaptation, and multimodality, this article puts forward a model of multimodal adaptation and uses that framework to evaluate Monkey King’s major reconstructions of immortals in a transnational context. Focusing on explicit and implicit adaptations, the article discusses how the new presentations of these immortals deviate from those in Chinese culture, and how a world that would appear to be turned upside down, in the eyes of a Chinese audience, comes into being. The article also sheds some light on the effect of transnational adaptations on the culture of origin for the source text.